Mengubah Bungkil Sawit Dan Kotoran Sapi Mejadi Maggot (Hermetia illucens ) dan Media Organiknya Sebagai Pelet Ikan - Syahrizal, Syahrizal; safratilofa, safratilofa; Purnama, Rizal (Universitas Batangahari Jambi, 2024)
Feed for fish is one of the main factors determining the survival of fish to achieve normal life. The feed design was prepared as a test pellet application in catfish (Clarias gariepinus B) experiments. This study aims to analyze converting palm meal and cow dung into maggot (Hermetia illucens) and its organic media as fish pellet feed. The occurrence of pellet raw materials is processed from fermentation of oil palm meal (BKS) and cow dung (KS) during the life cycle of BSF (Black Soldier Fly) fruit fly 21 days. The design used was a Complete Random Design of 4 treatments and 3 repeats, with the implementation of treatment A (BKS 100.00% : KS 00.00); B (BKS 50.00% : KS 50.00%), (BKS 75.00 % : KS 25.00%) and (BKS 00.00 % : KS 100.00%). The results of this study were variable parameters for the average weight and length of the best maggots in treatment A (0.25 g / head) and (1.54 cm), the lowest in treatment D (0.18 g / head. and 0.95 cm). Maggot biomass production was also highest in treatment A (157.33 heads/2.5 kg substrate) and lowest in treatment D (89.00 heads/2.5 kg substrate). The bioconversion value of maggot into ESE organic matter (organic substrate efficiency) was highest in treatment A (6.29%) and lowest at D (3.56%), the residual value of ESE bioconverts was highest D (56.60%) and lowest A (45.39%). The pellet production results from maggot biomass and the best organic media were treated respectively A (564.33 grams), B (486.67 grams), C (367.00 grams) and D (362.33 grams).